2017
DOI: 10.1186/s12884-017-1404-7
|View full text |Cite
|
Sign up to set email alerts
|

A cost effectiveness analysis of midwife psycho-education for fearful pregnant women – a health system perspective for the antenatal period

Abstract: BackgroundPsycho-education can reduce childbirth fear and caesarean section numbers. This study determines the cost-effectiveness of a midwife-led psycho-education intervention for women fearful of birth.MethodOne thousand four hundred ten pregnant women in south-east Queensland, Australia were screened for childbirth fear (W-DEQ A ≥ 66). Women with high scores (n = 339) were randomised to the BELIEF Study (Birth Emotions and Looking to Improve Expectant Fear) to receive psycho-education (n = 170) at 24 and 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 32 publications
1
22
0
4
Order By: Relevance
“…Another study on women with high childbirth fear indicated that the overall caesarean section rates decrease after undergoing BELIEF clinically [21]. In addition, BELIEF seems to be a cost-effective approach [22].…”
Section: Introductionmentioning
confidence: 99%
“…Another study on women with high childbirth fear indicated that the overall caesarean section rates decrease after undergoing BELIEF clinically [21]. In addition, BELIEF seems to be a cost-effective approach [22].…”
Section: Introductionmentioning
confidence: 99%
“…Another study on women with high level of childbirth fear indicated that after implementing BELIEF, fearful women show clinically signi cant reduction in overall caesarean section rates than control group women (21). In addition, costeffectiveness of the BELIEF has been established (22). However, we do not aware of any published study that explore effectiveness of psychoeducational intervention on childbirth fear among Iranian women.…”
Section: Introductionmentioning
confidence: 91%
“…As reviewed, midwife-led continuity care starting from pregnancy until early parenting period with home services, has been associated with positive maternal outcomes and parents' satisfaction [28]. Importantly, the resulted positive maternal outcomes had contributed to reduced health care cost [29]. Unfortunately, in Singapore, there is no midwife-led continuity care service to help rst-time parents in gaining positive parenting experience and building PSE.…”
Section: Introductionmentioning
confidence: 99%